(untitled) (Praxis Educativa, 2012)
This paper presents some results of a research on discourses about “natives” in the context of a secondary school in Córdoba, Argentina. This research was developed during 2006-2007, and it was focused on the analysis of a pedagogical project that considered on the topic of “cultural diversity” and “indigenous people” in order to design educational strategies of intervention to improve and/or transform pedagogical practices. These results mainly discuss the relationship between school and cultural difference in the context of the significant political, economic and cultural changes that took place from the 90’s.